2017
DOI: 10.3748/wjg.v23.i20.3713
|View full text |Cite
|
Sign up to set email alerts
|

Study on the value of serum miR-106b for the early diagnosis of hepatocellular carcinoma

Abstract: AIMTo analyze the incidence of hepatocellular carcinoma (HCC) in a population that underwent health checkups and had high serum miR-106b levels.METHODSA total of 335 subjects who underwent checkups in the Digestive and Liver Disease Department of our hospital were randomly selected. RT-PCR was used to detect the level of miR-106b in serum samples. Laboratory and imaging examinations were carried out to confirm the HCC diagnosis in patients who had a > 2-fold change in miR-106b levels. Ultrasound-guided biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Interestingly, among all validated miRNAs, miR-106b-3p was the only one to show an up-regulation both in plasma and serum samples. These results are in agreement with recent reports [ 52 , 53 ]. In HCC, miR-106b and miRNAs of the miR-106b-25 cluster are upregulated, promote cell migration and metastasis and are associated with poor prognosis [ 54 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, among all validated miRNAs, miR-106b-3p was the only one to show an up-regulation both in plasma and serum samples. These results are in agreement with recent reports [ 52 , 53 ]. In HCC, miR-106b and miRNAs of the miR-106b-25 cluster are upregulated, promote cell migration and metastasis and are associated with poor prognosis [ 54 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…Several previous studies have confirmed that some of these miRs were differentially expressed in HCC patients versus their normal counterparts. For instance, the serum level of miR-106b was higher in HCC patients at advanced versus early stages with ROC value of 0.885 [24]. Using miR-107 as a diagnostic marker, it separates HCC patients from normal subjects and the combination of miR-92 and miR-3126 improved their diagnostic accuracy [25].…”
Section: Discussionmentioning
confidence: 99%
“…They can be found in circulation enclosed in EVs or associated with proteins (typically argonaute 2 (AGO2) and nucleomorphin 1 (NPM1)) or lipoproteins (e.g., HDL). Many circulating miRNAs, including miR-106b, miR-21, miR-200a, miR-122, miR-223, let-7f, and miR-155 have already been described to associate with HCC, with promising diagnostic and prognostic value [127,128]. Overall, more than 70 miRNAs have already been suggested as candidate biomarkers for HCC [129].…”
Section: Cfdnamentioning
confidence: 99%